A Novel Phosphorus Repletion Strategy in a Patient With Duodenal Perforation. (June 2014) - Kemmerly, Thomas; Vuong, Carolyn; Kaunitz, Jonathan D.
We describe a case in which a patient receiving parenteral nutrition (PN) developed hypophosphatemia. Due to lack of availability of parenteral phosphate supplements, we chose to restore phosphate using diluted hypertonic sodium phosphate enemas. Due to the recent shortages of parenteral minerals and vitamins, such an alternate means of repletion is of increasing importance. Diluted hypertonic sodium phosphate enemas are inexpensive, easy to administer, and effective since phosphate is readily absorbed across the rectal mucosa. We hope that through this type of repletion, life-threatening hypophosphatemia among patients receiving PN can be avoided.